(untitled) (The Pakistan Development Review, 2016)
It is a matter of great honour for me to deliver the Quaid-i-Azam memorial lecture. He is an everlasting source of inspiration for me due to his two unmatched attributes, i.e. tolerance and determination. To me, this combination of qualities in Jinnah made him a symbol of glory and grandeur. Tolerance in particular can play an instrumental role in changing a society’s outlook, and Jinnah set an example for us for being an emblem of tolerance. Tolerance with all its manifestations in different facets of life is direly needed in our society. For instance, religious, ethnic and racial tolerance can be considered as the first step towards forming a sound and rational society. In the same way, this gathering today has given me immense satisfaction, as different views from different schools of thought are assimilated and tolerated.